Spiritual assistance in palliative care as a professional career - Chemin, Marcia Regina Chizini (2020)
The therapeutic approach of Palliative Care provides attention to the spiritual aspects of the diseased person and their family members according to the ethical intention of offering comprehensive care. The composition of the multidisciplinary palliative care teams includes the participation of a Spiritual Assistant; however, it is not established who or which professional should occupy this function. The literature on this subject does not answer this question. In order to examine the possibility of the professional action of a Theology graduate as responsible for this Spiritual Assistance, the analysis of the national curriculum guidelines for courses in Theology and opinions of the Ministry of Education was made. It was concluded that Theology courses can prepare people to act as spiritual assistants and that this can be a professional career.